Response of scented rice landraces of North Bengal under organic nutrient management in Darjeeling hills - Karki, Sanjivani; Ghosh, Mrityunjay; Chettri, Binoy; Ghimiray, TS; Banerjee, S; Biswas, P; Bag, A (ORYZA-An International Journal of Rice, 2023)
The traditional practice of growing scented rice in Darjeeling Himalayas needs refinement in nutrient management for sustained production with desired quality. The effect of organic nutrient sources (Cow dung manure @ 5 t/ha, Vermicompost @ 1.5 t/ha, Mustard cake @ 0.5 t/ha, and Leaf mould @ 1 t/ha) on two aromatic rice cultivars (Kalture, and Kalonunia) was studied in a split-plot design during wet (kharif) season of 2021 at Uttar Banga Krishi Viswavidyalaya, Kalimpong, West Bengal. Kalture had taller plants (137.1 cm) and lodging susceptibility (score 4.0) at harvest, while Kalonunia remained unlodged. Kalonunia produced 16.1% greater grain yield (3.32 t ha-1 vs. 2.86 t ha-1) over Kalture due to more number of panicles m-2 (356.2) and filled grains panicle-1 (90.1). Both aromatic rice cultivars had medium-slender (MS) white kernels, but Kalonunia had higher protein content (7.3%), alkali spreading value (score 6.0) and aroma (score 1.8) than Kalture (6.7%, score 5.7 and score 1.6). The application of vermicompost @ 1.5 t ha-1 resulted in higher grain yield (3.22 t ha-1), but mustard cake @ 0.5 t ha-1 might be better option due to moderate yield (3.11 t ha-1), better grain quality, and greater residual N (235.1 kg ha-1), P status (23.4 kg ha-1) in hill soil of West Bengal.